A study of age related retention of individual characteristics in handwriting - Mohamad Mahatidr, Amir Sultan (Universiti Sains Malaysia, 2009)
Handwriting and signature have been much involved in human life. It serves as the basic tool in education, recording of information, exchange of knowledge, communication and personal identification. Even in the wake of the modem digital world of computerization, the importance of handwriting and signature are still undisputed and cannot be neglected. This makes handwriting and signature as a form of evidence which gain high interest in the field of Forensic Science. The document examination has been using and proving the identity of the author and also revealing any mean of forgery. Researchers and experts have studied and explained various individual characteristics which are used as the cue for positive identification and detecting the attempt of forgery. Various factors which influence handwriting and signatures had been discovered as physical factors, medication, mental states, aging and so on. Aging is an important factor in forensic investigation. Humans undergo vanous changes in the aspect of physical as well as psychological as aging proceeds. This may produce significant changes in the handwriting and signature of an individual. The credibility and probative value of this evidence may be disputed due to this reason. Hence, this research is aimed to explain the age related retention on the individual characteristics of handwriting and signatures. This study involves qualitative assessment and analysis of handwriting or signature samples which are influenced by aging. The variable aging is assessed by analyzing samples executed in different times of interval (past and recent) with. The parameters used to identify the individual characteristics include termination, design of letters, location of dots and so on. The individual characteristics are marked for the comparison between past and recent samples by mean of comparison chart which shows the retention of the individual characteristics. The result of the study proved the retention of the individual characteristic in one's handwriting or signature even after aging. This study may increase the probative value of handwriting and signature evidences which have aging influenced. The retention of the individual characteristics can be very well recognized and identified. This can later be used for analysis and identification.